2005
DOI: 10.1007/s10750-004-4959-z
|View full text |Cite
|
Sign up to set email alerts
|

Habitat diversity and ostracod distribution patterns in Belarus

Abstract: Ostracod diversity and abundance was studied in 10 different types of water bodies of Belarus (bogs, brooks, canals, oxbows, ponds, reservoirs, rivers, springs, shoal of lake and temporary pools). Hydrochemical variables, sediment, and vegetation were analyzed. In total 156 different localities were investigated. Habitat diversity was based mainly upon the closely correlated hydrochemical variables of mineralization (hardness total and carbonate, conductivity, total value of dissolved substances), although bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Many of the taxa collected in this study were cosmopolitan and able to tolerate a broad range of water quality conditions (Ingram et al, 1997), and the high conductivity or turbidity in some treatments was unlikely to represent a threshold to colonization. Similarly, a study examining ostracod distributions in Belarus found that many of the species were well known and widespread, and that distribution patterns were less influenced by abiotic conditions than by biotic interactions (Nagorskaya & Keyser, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the taxa collected in this study were cosmopolitan and able to tolerate a broad range of water quality conditions (Ingram et al, 1997), and the high conductivity or turbidity in some treatments was unlikely to represent a threshold to colonization. Similarly, a study examining ostracod distributions in Belarus found that many of the species were well known and widespread, and that distribution patterns were less influenced by abiotic conditions than by biotic interactions (Nagorskaya & Keyser, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…While physical structure can have a strong influence on aquatic macroinvertebrate community structure, other studies have indicated that other factors may also affect the relative abundance of macroinvertebrates (Therriault & Kolasa, 1999;Ruetz et al, 2002;Nagorskaya & Keyser, 2005;Srivastava, 2006). Community structure may also be influenced by food resources (Campeau et al, 1994;Warren & Spencer, 1996) and water quality (Spieles & Mitsch, 2003;Burdett et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Outside Mexico it has been collected in USA (Forester et al, 2013), Belarus (Nagorskaya, 2002;Nagorskaya, & Keyser, 2005), Europe (Marmonier, & Chatelliers, 1992;Horne, 2007;Szlauer-Lukaszewska, 2012) and in the Arctic (Wetterich, 2008).…”
Section: Morphologymentioning
confidence: 99%
“…Wetterich (2008) suggests that this species is oligohalophilic. This species has been collected in oxbow lakes, ponds and rivers and shows a preference for sandy and silty substrates (Nagorskaya, & Keyser, 2005). It has been collected among Phragmites australis rushes (Szlauer-Lukaszewska, 2012).…”
Section: Morphologymentioning
confidence: 99%
“…Ostracods have been reported to colonize a variety of habitats (Nagorskaya and Keyser, 2005), including deep-lake areas (Griffiths et al, 1993), and can tolerate low levels of DO (De Dekker, 2002). C. patzcuaro prefers sediments rich in organic matter and has a high capacity to adapt, and it exhibits broad tolerance to the adverse conditions present by deep-lake areas (Decrouy, 2009).…”
Section: Adaptation To Profundal Life In Alchichicamentioning
confidence: 99%